Research advances in biology, ecology and management of rice planthoppers - KUAI Peng; LOU Yonggen (浙江大学学报. 农业与生命科学版, 2022)
Rice planthoppers, mainly including Nilaparvata lugens, Sogatella furcifera, and Laodelphax striatellus, are one of the most important insect pests of rice in China. In this review, we summarized the latest research progress on the molecular basis of important genetic characteristics (wing-morph differentiation, fecundity, insecticide resistance) of rice planthoppers, interactions among rice, rice planthoppers, natural enemies of rice planthoppers and other organisms, mechanisms underlying rice planthopper outbreak, and management of rice planthoppers. Finally, we suggest that future studies should further dissect the molecular basis of biology and ecology related to rice planthopper outbreak, and find the coordination mechanisms between intensified agriculture and rice ecosystem resistance at the micro level, so as to maintain or improve the rice ecosystem resistance, and achieve sustainable management of rice planthoppers in the context of intensified agriculture.